Autoantibodies' titre modulation by anti-BlyS treatment in systemic lupus erythematosus. (August 2019) - Cavazzana, I; Kumar, R; Pozzari, C; Ottaviani, R; Fredi, M; Piantoni, S; Andreoli, L; Tincani, A; Franceschini, F
Objective: The objective of this study was to analyse autoantibodies' titres modulation during belimumab treatment in 50 patients with systemic lupus erythematosus (SLE). Methods: Sera were collected at belimumab start (T0) and every six months until the 24th month. Disease activity index (SLEDAI-2K) was analysed at every timepoint. High avidity anti-dsDNA was detected by radioimmunological method, anti-ENA, anti-cardiolipin antibodies (aCL), anti-β2 glycoprotein I (anti-β2GPI) were analysed by ELISA. Results: Fifty patients with SLE (mean SLEDAI-2K: 7.18 ± :3), mean age of 39 ± 11 years and mean follow-up of 13 ± 7.8 years were enrolled. A significant decrease of anti-dsDNA and anti-β2GPI IgM titres was observed at all timepoints. IgG aCL titre showed significant decrease only at T18. Anti-dsDNA negativization was detected in 21%, anti-β2GPI IgG in 33% and aCL IgG in 30% of sera, mostly at T6. Anti-ribosomal showed a significant titre decrease at T6 and T12, with negative seroconversion at T18. Anti-Sm titre significantly dropped down at T6, then remained stable during the time. Significant correlations were found between anti-dsDNA and anti-ribosomal titre and between SLEDAI ratio (SLEDAI value/SLEDAI T0) and anti-ribosomal titre ratio (value/value T0). Conclusions: Belimumab treatment induced a significant reduction of SLE-specific autoantibodies titre and IgM anti-β2GPI. Anti-ribosomal titre decrease correlates with anti-dsDNA titre and disease activity improvement.